PENGINTEGRASIAN KEYAKINAN AGAMA PADA PEMBELAJARAN IPA DI SEKOLAH DASAR - Tursinawati; Ari Widodo; Wahyu Sopandi; Hasbi Amiruddin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
Up to now the integration of religion and science in the implementation of learning is often neglected. Whereas, these two aspects are part of the curriculum and educational objectives. The study in this article is aimed to examine the integration of religious beliefs in achieving the knowledge on natural science teaching and learning that is applied by elementary school teachers so far. The research method is a case study with the elementary school teacher as the research subject. The sources of data are observations, interviews, and questionnaires. The data analysis technique used is descriptive quantitative for the questionnaire and analyzed to in-depth qualitative data entirely. The findings showed that up to now elementary school teachers have integrated religious beliefs and science by relating the verses of the Al-Qur'an to the natural science learning materials, but they rarely integrated students' religious beliefs in achieving scientific knowledge in natural science learning. Teachers have often difficulties integrated religious and scientific beliefs in applying methods, time management, and teaching and learning materials. Teachers sometimes applied teaching strategies such as motivating students, giving apperception and using the methods to integrate the religious beliefs into natural science learning. The teachers have not ever applied any assessment yet related to the religious beliefs in natural science learning. Students are sometimes active to be involved in the discussion and question and answer session about the religious beliefs in achieving their science and knowledge in natural science learning class. The integration of religious beliefs in natural science learning should be implemented explicitly in order to make these two aspects become a unified whole curriculum.